2017
DOI: 10.1152/ajplung.00347.2016
|View full text |Cite
|
Sign up to set email alerts
|

Aging exacerbates acute lung injury-induced changes of the air-blood barrier, lung function, and inflammation in the mouse

Abstract: Acute lung injury (ALI) is characterized by hypoxemia, enhanced permeability of the air-blood barrier, and pulmonary edema. Particularly in the elderly, ALI is associated with increased morbidity and mortality. The reasons for this, however, are poorly understood. We hypothesized that age-related changes in pulmonary structure, function, and inflammation lead to a worse prognosis in ALI. ALI was induced in young (10 wk old) and old (18 mo old) male C57BL/6 mice by intranasal application of 2.5 mg lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…These changes fit with our observations in lung function measurements, where an increase in tissue resistance (G) and hysteresis was detected. G is an inverse measure of compliance in the parenchymal lung tissue and its increase in ALI, related to septal edema formation, has been shown previously [29]. Hysteresis might increase due to changes in tissue resistance and elastance or due to changes in surfactant composition [30,31].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…These changes fit with our observations in lung function measurements, where an increase in tissue resistance (G) and hysteresis was detected. G is an inverse measure of compliance in the parenchymal lung tissue and its increase in ALI, related to septal edema formation, has been shown previously [29]. Hysteresis might increase due to changes in tissue resistance and elastance or due to changes in surfactant composition [30,31].…”
Section: Discussionmentioning
confidence: 68%
“…The control mice received equal volume of saline solution (n = 7 per group). The animals were sacrificed 24 h after the induction of ALI, as described previously [29]. All animal procedures were approved by the Lower Saxony State Office for Consumer Protection and Food Safety (LAVES; Authorization number: 33.9-42502-04-14/1623, Approval Date: 26/09/2014) in accordance with the German law for animal protection and with the European Directive, 2010/63/EU.…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging also causes impaired alveolar barrier integrity after lung injury. In comparison with young mice, old mice had increased response of acute lung injury in association with decreased expressions of tight junction protein after lipopolysaccharide insult [86]. Yin et al demonstrated that aged mice had increased susceptibility to influenza viral pneumonia with exacerbated damage and delayed repair of alveolar epithelial cells (AECs) [87].…”
Section: The Impacts Of Aging In Respiratory Tract Antimicrobial Dmentioning
confidence: 99%